Application of deep eutectic solvents in the extraction and separation of target compounds from various samples. Issue 6 (5th February 2015) - Tang, Baokun; Zhang, Heng; Row, Kyung Ho
Abstract : Deep eutectic solvents, as a new type of eco‐friendly solvent, have attracted increasing attention in chemistry for the extraction and separation of target compounds from various samples. To summarize the application of deep eutectic solvents, this review highlights some of the unique properties of deep eutectic solvents and deep‐eutectic‐solvent‐based materials, as well as their applications in extraction and separation. In this paper, the available data and references in this field are reviewed to summarize the application developments of deep eutectic solvents. Based on the development of deep eutectic solvents, the exploitation of new deep eutectic solvents and deep‐eutectic‐solvent‐based materials are expected to diversify into extraction and separation.